THEORETICAL ASPECTS OF THE RELATIONSHIP BETWEEN LAW AND ETHICS (International Conference on Modern Science and Scientific Studies, 2025)
This article examines the role of law and ethics in social life, their similar and different aspects, as well as their theoretical foundations. The interrelationship between law and ethics is analyzed based on normativist, natural law, and sociological approaches. Additionally, the expression of moral values in the Constitution and laws, the role of national customs and traditions in legal creativity, and the importance of ethical norms in judicial practice are considered. Our research shows that the harmony between law and ethics is an important factor in ensuring social stability and justice.